The Role Of Social Accounting in The Empowerment Of Mustahik at Rumah Zakat Kediri - ricky abiawan Sandi; Sri Luayyi; M. Alfa Niam (LP2M IAIN Palopo, 2025)
This study aims to analyze the role of social accounting in supporting the effectiveness of mustahik empowerment programs at Rumah Zakat Kediri. The research employs a qualitative approach with a phenomenological design. Data were collected through semi-structured interviews, observations, and documentation involving amil, mustahik, and other stakeholders supporting the empowerment programs. The findings indicate that the implementation of social accounting at Rumah Zakat Kediri has been effective in enhancing transparency, accountability, and social responsibility within empowerment programs. Transparency is reflected through open access to zakat collection and distribution reports via various digital media platforms. Accountability is realized through internal and external audits, as well as supervision by the Sharia Supervisory Board and the Ministry of Religious Affairs. Social responsibility is demonstrated by involving mustahik in the planning, implementation, and evaluation of programs, thereby creating participatory and sustainable relationships. The application of social accounting contributes to improving economic independence, social participation, and public trust in zakat institutions. This research provides new insights into the practical implementation of social accounting in Islamic philanthropy, highlighting its transformative role not only as a reporting mechanism but also as a medium for social change and institutional legitimacy in achieving the objectives of zakat for sustainable community welfare.